Regional Differences in the Absorption of Financial Support by Agricultural Holdings and Changes in the Level of Agriculture in Poland in the Years 2004–2009 - Rudnicki, Roman; Kacprzak, Ewa; Dubownik, Anna (Regional Barometer. Analyses & Prognoses, 2013)
The article offers an analysis of the volume of financial support absorbed by agricultural holdings in Poland against the background of changes in the level of farming during the country’s EU membership (the years 2004–2009). The transfer of EUR 21 billion of assistance contributed to the development of Polish farming to a limited extent only. This was largely due to the structure of the funds being unfavourable from the point of view of the development of agriculture, in particular because of a large proportion of passive forms of EU support (area payments). Of no little importance was also the fact that some of the operational measures were intended to improve the natural environment and put farms on a non-agricultural development path rather than bring about an increase in the production level and competitiveness of agriculture.